Improving Adherence to Taking Medication through Family Support for Hypertensive Elderly in the District Area of the Patient - Fauzia, Wilda; Mandaty, Fandy Aldi (STIKes RSPAD RSPAD Gatot Soebroto, 2023)
Age isa period of human growth that is prone to various health problems such as hypertension. Hypertension is also the highest incidence of non-communicable diseases (NCDs) compared to other NCDs, which is 76.5% in Central Java Province. Uncontrolled hypertension can lead to more serious health problems. Management of hypertension requires the elderly to take medication regularly. Elderly compliance is the key to success in controlling blood pressure. Family involvement in treatment certainly has a positive impact on the success of treatment therapy. Objective: to determine the relationship between family support and medication adherence in hypertensive elderly in Pati Regency. Research Method: A type of correlational descriptive quantitative research with a cross sectional approach. The population is all hypertensive elderly in Pati Regency and the number of samples is 44 elderly according to inclusion and exclusion criteria. Results: Seniors who received good category family support tended to be more compliant with taking medication. The results of statistical tests using the Chi Square test obtained a p value of 0.002 (<0.05). Conclusion: There is a relationship between family support and medication adherence in hypertensive elderly in Pati Regency.